Bahasa Inggris - Adwitiya Sarwahita, Salsabila; Usodo, Budi; Yamtinah, Sri (Universitas Veteran Bangun Nusantara, 2025)
This study aims to determine the effect of interest in learning mathematics on the ability of basic arithmetic operations in grade 1 students of Madrasah Ibtidaiyah. The background of this study is the low basic ability of students in mathematical operations, which is thought to be closely related to the low interest of students in learning the subject. The method used in this study is a quantitative approach with a correlational research type. Data were collected through a questionnaire on learning interests and tests on basic arithmetic operations. The sample in this study were grade 1 students from one of the Madrasah Ibtidaiyah who were selected purposively. The results of data analysis showed a positive and significant effect between interest in learning mathematics on the ability of basic arithmetic operations. The higher the students' interest in learning, the better their ability to complete basic arithmetic operations. Keywords: Learning Interest, Arithmetic Operations, Basic Arithmetic, Grade 1 Students